Design, development, optimization and Invitro evaluation of core-in-cup tablet coated with Eudragit FS30D for modulated release of Mefenamic acid in colon. - K. MALLESWARI,; J. VIJAYA RATNA, (International Journal of Pharma and Bio Sciences, 2018)
Colonic delivery has gained increasing importance for the delivery of drugs for the treatment of local diseases.To achieve a successfull colonic delivery a drug needs to be protected from absorbtion in the GI tract and abruptly release in to the proximal colon which is considered the optimum site for colon-targeted delivery of drugs.The purpose of this study is to explore the possibility of core in cup tablet as a novel carrier for colonic delivery system of a sparingly soluble drug, Mefenamic acid. The study involves designing a tablet for colon-target which consists of a central blended form of drug and polymer core and is coated to thin film and fine thicknesses with Eudragit FS30D, and finally the core-in-cup is over coated with Eudragit FS30D to provide acid and intestinal resistance. Drug release study in simulated pH7.4 phosphate buffer (colonic fluid) revealed the delayed release nature of Eudragit coating. Drug release kinetic data proved that the optimized colon drug delivery system was fitted well into first-order model, and apparent lag time was found to be 5 hours, followed by peppas release kinetics. Correlation coefficient (r2) = 0.9999, Values are of mean standard deviation(n=3) p<0.01 when compared with blank